2022
DOI: 10.3390/sports10050078
|View full text |Cite
|
Sign up to set email alerts
|

Change in BMI and Fitness among Primary School Children in Austria: A 24-Month Follow-Up Study of 303 Children Measured before and during the Ongoing COVID-19 Pandemic

Abstract: The ongoing COVID-19 pandemic not only impacted the health of school children directly through SARS-CoV-2 infections, but the associated closures of schools and sports facilities also resulted in long-term negative side effects. The aim of this study was to investigate the effects of COVID-19-related mitigation measures on the health and fitness status of primary school children in Austria. A total of 303 primary school children participated in the longitudinal study. Data on height, weight, and fitness were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…The curve was measured in cm by bending the upper body based on the baseline, which left a forward curve measured in a seated state [ 15 ]. Obesity status was determined based on body mass index, which was calculated using each participant’s height and weight [ 16 ]. Students’ physical fitness levels were measured based on their overall health and physical fitness scores by adding scores in five areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curve was measured in cm by bending the upper body based on the baseline, which left a forward curve measured in a seated state [ 15 ]. Obesity status was determined based on body mass index, which was calculated using each participant’s height and weight [ 16 ]. Students’ physical fitness levels were measured based on their overall health and physical fitness scores by adding scores in five areas.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, a study on physical fitness changes in the midst of the COVID-19 situation was conducted on students in Japan, China, and Austria. Most students reported that their physical fitness levels were decreasing [ 15 , 16 , 17 , 18 ]. Moreover, various studies have examined educational, in addition to physical, aspects that have changed because of the COVID-19 situation.…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal evaluation as lockdown measurements were eased and schools partially reopened (10 months between 1st and 2nd visit) revealed that relaxation of restrictive measures were not enough to reverse the effects of the lockdown on weight gain. Few studies evaluated the long-term effects of lockdown: a recent study also reported sustained and signi cant weight gain for one year in Korean children, although schools were fully open for the last six months [28]; another study showed an important weight gain increase the rst year of the pandemic followed by a period of stabilization [29] and a retrospective chart review study reported that excessive weight gain in 2020 did not reverse by 2021 [30]. We also observed that boys, unlike girls, continued gaining weight although lockdown measurements were eased.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the excess weight gained by children could be di cult to reverse and might contribute to overweight (OW) and obesity (OB) in adulthood [27]. To our knowledge, few prior studies examined the long-term consequences of prolonged lockdown in body weight [28,29,30]. The objective of this longitudinal study was to examine changes in body weight, lifestyle and HRQoL in children for almost two years after the beginning of the COVID-19 pandemic lockdown in Argentina, where a very long period of strict lockdown was followed by almost one year of gradual opening.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of these studies are mixed and need to be clearer [ 11 , 15 ]. Additionally, to the best of our knowledge, there is still little longitudinal data reporting the potential impact of pandemic lockdowns and other restrain measures (e.g., school closure) on people’s physical fitness parameters (e.g., speed, flexibility, aerobic fitness) [ 11 , 14 , 15 , 16 ]. Importantly, the longitudinal nature of these data is paramount to exploring how time spent in lockdown and after lockdown can influence adolescents’ physical fitness patterns over time.…”
Section: Introductionmentioning
confidence: 99%